Sistem Pakar Berbasis Web Menggunakan Metode Backward Chaining untuk Menentukan Nutrisi Yang Tepat Bagi Ibu Hamil - Yuvidarmayunata Yuvidarmayunata (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
Expert System is a computer-based system that uses knowledge, facts and reasoning techniques in solving problems that normally can only be solved by an expert in the field. Many cases can be used as research in Expert Systems, one diagnosis of proper nutrition. In this study we will design an expert system to diagnose the type of proper nutrition for pregnant women. Determining the proper nutrition for pregnant women is important to note because it causes birth defects and infant mortality. In this study, the system uses the Backward Chaining method in determining the proper nutrition for pregnant women. This system can provide the right solution for pregnant women. This application is made to the programming language PHP and MySQL as its knowledge base storage. System testing is done by matching the search process Backward Chaining in the decision tree to determine the proper nutrition for pregnant women at the design stage to the actual system that has been built. Keywords : Expert System, diagnose, Backward Chaining, Nutrition, Pregnancy